Probabilistic Modeling of Occupational Health and Safety Culture Influence on Operational Safety in Petrochemical and Oil and Gas Facilities Using Bayesian Networks - Supardi; Jerry; Denny Hendrik Nainggolan (Testing Center for Oil and Gas LEMIGAS, 2026)
The oil and gas and petrochemical industries are characterized by high-risk operations involving complex processes, hazardous materials, and diverse working conditions. Therefore, a strong Occupational Health and Safety (OHS) culture is essential to promote operational safety. This study examines the effect of OHS culture on operational safety using probabilistic analysis based on Bayesian Network modeling. A quantitative explanatory research design is employed, with data collected from 78 industrial placement students at Politeknik Industri Petrokimia Banten who work in production and maintenance facilities of high-risk petrochemical and oil and gas companies in the industrial area of Cilegon, Banten, Indonesia. OHS culture is measured through four dimensions: management commitment, safety communication, risk awareness, and safety participation. Operational safety is assessed using indicators of safety behavior and near-miss reporting. The results show that OHS culture plays a significant role in determining operational safety, with safety communication exerting the greatest influence on safety performance. Probabilistic inference indicates that higher levels of OHS culture lead to safer operating conditions, while inadequate communication contributes significantly to poor safety performance. Sensitivity analysis further identifies communication as a key determinant of safety behavior and risk management.